2015
DOI: 10.1038/onc.2015.456
|View full text |Cite
|
Sign up to set email alerts
|

Excess of NPM-ALK oncogenic signaling promotes cellular apoptosis and drug dependency

Abstract: Most of Anaplastic Large Cell Lymphoma (ALCL) cases carry the t(2;5; p23;q35) that produces the fusion protein NPM-ALK. NPM-ALK deregulated kinase activity drives several pathways that support malignant transformation of lymphoma cells. We found that in ALK-rearranged ALCL cell lines NPM-ALK was distributed in equal amounts between the cytoplasm and the nucleus. Only the cytoplasmic portion was catalytically active in both cell lines and primary ALCL, whereas the nuclear portion was inactive due to heterodimer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
53
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(60 citation statements)
references
References 53 publications
5
53
2
Order By: Relevance
“…Therefore, these cells were kept in culture in the presence of 3-10 nmol/L lorlatinib. However, in contrast to previously described drug-addicted cells (26), NPM/ALK transcript levels were not substantially upregulated (Table 1; Supplementary Fig. S2).…”
Section: Alk-dependent Mechanisms Driving Resistance In Alcl Cells Incontrasting
confidence: 96%
See 2 more Smart Citations
“…Therefore, these cells were kept in culture in the presence of 3-10 nmol/L lorlatinib. However, in contrast to previously described drug-addicted cells (26), NPM/ALK transcript levels were not substantially upregulated (Table 1; Supplementary Fig. S2).…”
Section: Alk-dependent Mechanisms Driving Resistance In Alcl Cells Incontrasting
confidence: 96%
“…Whether this is due to inefficient dimerization with normal NPM1, or preferential binding to cytoplasmic proteins, is unclear at present and is under investigation. We speculate that the aberrant cytoplasmic localization of N1178H mutants functionally mimics an overexpressed fusion kinase, since the cytoplasmic fraction of NPM/ALK is thought to be the oncogenic driver (26), thus leading to resistance. This behavior may also explain the curious difference in Tyr1604 versus Tyr1278 uniquely observed in N1178H-mutated BD1 cells.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…An EEF1G-anaplastic lymphoma kinase (ALK) gene fusion was recently found in two pediatric patients with anaplastic large cell lymphoma (Palacios et al, 2017). In the context of the review, it is important that a fusion of the eEF1Bγ N-terminal domain provided exclusively cytoplasmic localization of the fusion protein (Ceccon et al, 2016) suggesting that the N-terminal domain of eEF1Bγ could not possibly be related to nuclear localization of eEF1Bγ alone.…”
Section: Eef1bγmentioning
confidence: 99%
“…We also observed that patients who harbored the NPM1-ALK fusion would be likely to achieve CR, especially when the fusion-type was exon 4 of the NPM1 gene aligned to exon 20 of the ALK gene. based on a preclinical model, that temporary suspension of TKI administration might bene t patients with the NPM-ALK fusion who develop resistance, which is the so-called "drug holiday" therapy 27 . There is no clinical evidence supporting the effectiveness of such therapy.…”
Section: Discussionmentioning
confidence: 99%